Self-association and association of tri-n-butyl phosphate (TBP) in different diluents - Čomor Jožef J.; Kopečni Miroslav M.; Petković Đorđe M. (Journal of the Serbian Chemical Society, 1999)
The interaction of tri-n-butyl phosphate (TBP) with diluents and its self-association have been investigated. The corresponding equilibrium constants were determined and used to calculate the concentration of TBP monomer. The calculated TBP monomer concentrations correspond to the TBP activities published in the literature.